Disjuncts and Conjuncts: A Syntactic Type of Study to Evaluate Kurdish Students' Writing in English (At University Level) (Journal of the College of Education for Women, 2019)
The principal concern of this study is Disjunct and Conjunct adverbials in theEnglish language. The study sets out to explore and clarify the types, nature andstructure of disjuncts and conjuncts. It also aims at testing student's performance toevaluate the use and usage of the disjuncts and conjuncts in their written performance.Two tests, accordingly, were given to some fifty students of at the Dept. of English, atthe college of languages (third and fourth stages) in the University of Sulaimani. Thehypothesis that the study was based on are those students use disjuncts and conjunctshardly enough in their writings and when doing so, they generally tend to stick only tothe most commonly used and familiar ones to them. The ultimate findings of the studyshow that this hypothesis is proved.